National Library of Medicine Regional Medical Library Program - Schoolman, Harold M. (1972)
The National Library of Medicine is charged with the development and management of a National Biomedical Communications Network. The Regional Medical Library Program is a forerunner of such a network; the product and institutions involved will be critical elements in its evolution. The immediate objective of the RMLP, the facilitation of biomedical information transfer, presents a logistical problem requiring substantial commitment from the health sciences community and extensive cooperation among libraries in each region.